Iran’s seismic puzzle: bridging gaps in earthquake emergency planning and public awareness for risk reduction - Ciampi, Paolo; Giannini, Leonardo Maria; Hedayat, Sattar; Ziariati, Tina; Scarascia Mugnozza, Gabriele (Italian journal of engineering geology and environment, 2024)
Iran, one of the most seismically active countries globally, faces recurrent and devastating earthquakes, resulting in significant loss of life, and necessitating improved disaster management. This study adopted a mixed-methods approach, combining seismic data analysis and a nationwide survey, with the aim to assess Iran’s emergency planning and management in seismically active regions. Seismic data, sourced from various studies, was analysed using a geographic information system (GIS) to identify trends and patterns since 1903, focusing on events with magnitudes larger than 5.7 Mw from 2010 to 2023. Concurrently, an online questionnaire was administered to a random sample of 500 Iranians, in order to explore public awareness, preparedness, and perceptions of the country’s emergency readiness. Seismic analysis revealed disparities in the number of earthquake-related fatalities, depending on population density, infrastructure quality, and emergency response capabilities. The survey indicated a perceived lack of public awareness and preparedness, with only 11.5% of the respondents feeling adequately prepared for earthquakes. Findings indicated poor knowledge of active faults and mistrust in government initiatives related to seismic events. Despite recent advances, Iran’s disaster management system faces challenges that are rooted in financial constraints, technological barriers, and public mistrust. Analyses converge on enhancing stakeholder cooperation, investments in early warning systems, and enforcement of stricter urban planning and construction standards. Bridging gaps in public awareness and trust-building measures is crucial to fostering a bottom-up “earthquake preparedness culture.” The findings from this study can provide insights for policymakers, emergency managers, and stakeholders to strengthen Iran’s resilience to earthquakes.